The Implementation of Cooperative Learning Mod to Increase Students' Learning Results in IPS Materials of Economic Activities at Grade IV SDN 06 Bukit Gadang - Efrianis, Efrianis (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2023)
This research concerns the effect of using the NHT Cooperative Learning learning model on student learning outcomes in social studies class IV SDN 06 Bukit Gadang. One of the materials taught in class IV SDN 06 Bukit Gadang Semester I is economic activity. In this material the authors found problems in class, namely the low learning outcomes obtained by students. From the initial test, the following results were obtained: of the 22 students who completed, only 8 (36.36%) completed, while 14 (66.64%) had not completed. To overcome this problem, the researchers made improvements to learning by using the NHT Type Cooperative Learning learning model. This model is a model that increases cooperation and responsibility between students in study groups by collaborating with their friends in solving problems and being able to answer questions given by the teacher based on the order of each number. Students work in study groups and are able to answer teacher questions based on the number called. At the end of Cycles I and II, individual tests were held using the NHT Type Cooperative Learning learning model, which was expected to improve the learning outcomes of Class IV students at SDN 06 Bukit Gadang. After learning was carried out using the NHT Type Cooperative Learning learning model, there was an increase in learning outcomes. From the initial data, the average value obtained by students was 66.86 in the pre-cycle, which increased to 73.77 at the end of cycle I and increased to 83.64 at the end of cycle II. Besides that, there was also an increase in the percentage of learning completeness. In the initial data with a total of 20 students, only 36.36% of students who completed, at the end of cycle I the number of students who completed increased to 54.55% and at the end of cycle II the students who completed increased to 86.36%.